Answer:
The answer is D
Explanation:
In order to find out the inverse of the function, you have to express a new function where the independent variable must be "y" instead of "x".
So, you have to reorganize the base function and then free the variable "x".
![f(x)=2^x+6\\f(x)=y\\y=2^x+6\\2^x=y-6\\log_2(2^x)=log_2(y-6)\\x*log_2(2)=log_2(y-6)\\log_2(2)=1\\x=log_2(y-6)\\](https://img.qammunity.org/2020/formulas/mathematics/college/dk87ml8b2036k28wxyad5qssefaovhjyt8.png)
Then, we recall "y" as "x" and
![x=f^-^1(x)](https://img.qammunity.org/2020/formulas/mathematics/college/yg46i0r2mkpnrdam0o1ns6sa51cuqjssn5.png)
Finally, the answer is:
![f^-^1(x)=log_2(x-6)](https://img.qammunity.org/2020/formulas/mathematics/college/htj3i7potap10my7h73zjfx8416584xyk3.png)